Accelerating water dissociation kinetics by isolating cobalt atoms into ruthenium lattice. Issue 1 (December 2018) - Mao, Junjie; He, Chun-Ting; Pei, Jiajing; Chen, Wenxing; He, Dongsheng; He, Yiqing; Zhuang, Zhongbin; Chen, Chen; Peng, Qing; Wang, Dingsheng; Li, Yadong
Abstract Designing highly active and robust platinum-free catalysts for hydrogen evolution reaction is of vital importance for clean energy applications yet challenging. Here we report highly active and stable cobalt-substituted ruthenium nanosheets for hydrogen evolution, in which cobalt atoms are isolated in ruthenium lattice as revealed by aberration-corrected high-resolution transmission electron microscopy and X-ray absorption fine structure measurement. Impressively, the cobalt-substituted ruthenium nanosheets only need an extremely low overpotential of 13 mV to achieve a current density of 10 mA cm−2 in 1 M KOH media and an ultralow Tafel slope of 29 mV dec−1, which exhibit top-level catalytic activity among all reported platinum-free electrocatalysts. The theoretical calculations reveal that the energy barrier of water dissociation can greatly reduce after single cobalt atom substitution, leading to its superior hydrogen evolution performance. This study provides a new insight into the development of highly efficient platinum-free hydrogen evolution catalysts. Water splitting provides an appealing route to generating carbon-neutral fuel, however the scarcity and cost of platinum, often used as a catalyst, necessitates a search for alternatives. Here, authors show cobalt atoms in ruthenium nanosheets to afford excellent hydrogen production activities.